Variation of Solar Wind Parameters During Intense Geomagnetic Storms - Subedi, Ayush; Adhikari, Binod; Mishra, Roshan Kumar (Himalayan Physics, 2017)
Geomagnetic disturbances are caused by enhanced solar wind magnetospheric energy coupling process. The principal cause of geomagnetic disturbance is the magnetic reconnection that establishes an electrodynamical coupling between the solar wind plasma and magnetosphere. Around solar maximum, the main structures emanating from the sun are sporadic Coronal Mass Ejection (CMEs) and their interplanetary counterparts (ICMEs). During the descending and minimum solar cycle phases, coronal holes occur more often. They appear as dark regions confined to Solar poles during the solar maximum but expand in size and moves toward the solar equator during the descending phase. In this work, we have taken three different geomagnetic storms during solar maxima. For the interpretation of events, we used interplanetary solar wind data and geomagnetic indices. These satellite data and Dst indices (ranging from -100nT to above) are interpreted by using the method of cross correlation. The values of Bz found approximately 20nT, -50nT and -20nT respectively. Similarly, the value of Dst is -250nT, -400nT and -300nT which shows very intense effect. Likewise, the correlation coefficient we obtained from this research work strongly suggest that interplanetary magnetic field Bz has strong impact for the cause of geomagnetic storms. The Himalayan Physics Vol. 6 & 7, April 2017 (80-85)